Técnicas de agrupamiento para métricas en difractogramas (2020)
In the present thesis starting from the dissimilarity introduced by Nicolás López, non-supervised algorithms are applied with the objective of finding natural groupings in the data of diffractograms and obtaining visual representations of the dataset. Clustering techniques like k-medoids or hierarchical clustering and also data representation algorithms like graph-oriented visualizations are implemented.